Peran Pendidikan Agama Kristen dalam Mengembangkan Karakter Siswa di Era Digital - Tambunan, Ruhut Parningotan; Arifianto, Yonatan Alex; Triposa, Reni (Jurnal Lentera Nusantara, 2024)
This research examines that where Christian religious education plays an important role in shaping student character in the digital era. Christian religious education provides a strong moral and spiritual foundation, and emphasises the values of honesty, responsibility and integrity to students. In facing the challenges of using technology, Christian religious education helps students to use technology wisely and ethically, so as to develop the ability to think critically in selecting and filtering the information they get. Using a descriptive qualitative method with a literature study approach, it can be concluded that the role of technology integration in Christian religious education allows for a more interactive and interesting teaching method, to deepen students' spiritual understanding. In addition, Christian religious education also plays an important role in shaping the adaptive and innovative character of students and preparing students to be able to face the development of the digital world with high morality.AbstrakPenelitian ini mengkaji bahwa peran penting pendidikan agama Kristen dalam membentuk karakter siswa di era digital. Pendidikan agama Kristen memberikan dasar moral dan spiritual yang kuat, serta menekankan nilai-nilai kejujuran, tanggung jawab, dan integritas kepada siswa. Dalam menghadapi tantangan pada penggunan teknologi, pendidikan agama Kristen membantu siswa untuk menggunakan teknologi secara bijaksana dan etis, sehingga dapat mengembangkan kemampuan berpikir secara kritis dalam memilih dan menyaring informasi yang di dapat. Menggunakan metode kualitatif deskritif dengan pendekatan studi literature maka dapat disimpulkan bahwaa peran integrasi teknologi dalam pendidikan agama Kristen memungkinkan sebagai metode pengajaran yang lebih interaktif dan menarik, untuk memperdalam pemahaman spiritual para siswa. Selain itu, pendidikan agama Kristen juga berperan penting dalam membentuk karakter siswa yang adaptif dan inovatif serta menyiapkan siswa untuk dapat menghadapi perkembangan dunia digital dengan moralitas yang tinggi.